Didactic culture as a scientific phenomenon, its structure and essential characteristics - Plaksin Andrii (Borys Grinchenko Kyiv Metropolitan University, 2015)
The article sets out a brief analysis of various research approaches to the interpretation of the concept of " didactic culture ", its content and structure by establishing a dialectical relationship of general culture and didactic culture; brief historical excursion ; developed and proposed to consider the author's didactic approach to the definition of culture as a scientific phenomenon.